Monitoring and disaster prevention of high and steep sandstone slopes along highways under construction - Liu, Xianlin; Lü, Xilin; Shao, Yu; Chen, Chuan; Liu, Guangbin; Li, Yishan; Li, Mingzhi; Wu, Xinyu; Chen, Youdong (Frontiers in Earth Science, 2024)
High and steep siltstone slopes along highway line are at high risk of disasters such as landslides, cracking of support structures, and so on. The monitoring, early warning, and emergency response of such slope disaster face enormous challenges, especially during the rainy season. In this paper, intelligent monitoring, early warning and forecasting system were carried out for the high steep siltstone slope with a transmission line tower at the slope crest along the highway under construction in Guangxi, China. The automatic monitoring data, emergency rescue program and rescue effect were analyzed, and emergency rescue measures for high steep slope protection were taken. The research results show that timely access to disaster warning information can effectively support the analysis of disaster causes and the evaluation of disposal programs. Deep-hole monitoring of deformation characteristics can determine the stable state of slopes, and the tangent angle warning criterion can be used for early warning and prediction of high steep slope landslides. By analyzing the location of the sliding surface and taking timely emergency disposal measures such as layered counterpressure method and micropipes, the landslide activities can be effectively controlled to prevent further acceleration of slope collapse. This study can provide an important reference for the monitoring, early warning, forecasting and emergency rescue of siltstone slopes along highways under construction.